Successful Treatment of Mucous Membrane Pemphigoid with Dupilumab: A Case Report - Zhiyi Wang; Xiaojing Liu; Jing Ni; Yushuo Qi; Zhiqi Song; Yongjun Piao (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)